Educational Ethics in Developing Character Learners - Marpaung, Syafri Fadillah; Sembiring, Ari Wibowo; Azzahra, Nindya; Hallawa, Syahfitri (Edumaspul: Jurnal Pendidikan, 2023)
Educational ethics is a moral foundation in developing students’ character. In this context, teachers are responsible for guiding students not only in academic aspects, but also in ethical values, integrity and social responsibility. Educational ethics includes the development of positive attitudes, morality, and interpersonal skills, all of which are important for forming a balanced person and contributing positively to society. In this process, teachers must pay attention to moral principles, justice and empathy in order to create a learning environment that supports the growth of good character in students. Teachers need to be role models in implementing ethical values, along with providing thought-provoking teaching. critical and moral reflection on students. The application of educational ethics also includes fair treatment of all students, without discrimination based on background or ability. In addition, learning should promote respect for diversity of cultures and views, helping students understand universal values, such as tolerance and cooperation. The importance of educational ethics lies in the formation of strong character in students, so that they can become responsible citizens and have integrity. In an ever-changing global context, teachers need to continually update their approaches in line with relevant ethical values to ensure that education is not just about knowledge, but also the formation of good character for future generations.